DAMPAK BENCANA GEMPA BUMI TERHADAP KONDISI SOSIAL EKONOMI MASYARAKAT DI KABUPATEN LOMBOK UTARA - Andrianus Andi; Laili Hurriati (JURNAL KOMPETITIF : MEDIA INFORMASI EKONOMI PEMBANGUNAN, MANAJEMEN DAN AKUNTANSI, 2020)
This study entitled "The Impact of Earthquakes on the Socio-Economic Condition of Communities on Lombok Nort ". In this study the researchers tried to try to study the phenomenon of the impact of the Lombok earthquake on the socio-economic conditions of the affected communities, especially North Lombok Regency.The type of this research is qualitative research with a documentation study approach, namely research conducted by looking at the documents that are then interpreted. Based on the results of the study, it can be explained about the socio-economic impact of the earthquake in Lombok in the affected communities, namely North Lombok District. from the socio-economic conditions of the community, which were many losses and damage that were affected by the people of North Lombok, both morally and materially, the Lombok earthquake had a significant impact on the conditions of Demography, health, education and the condition of the local housing area, especially in North Lombok Support. Nearly half of the population in North Lombok Regency who were displaced and several other people died, this has caused a large influence from the earthquake on the composition of the community's demography in North Lombok Regency. On the economic side, many people who lost their livelihoods, based on the results of the Lombok earthquake, especially for traders, who were originally able to earn 1-1.5 million per day but after the earthquake Lombok decreases their income by 50%. besides that, this earthquake caused a decrease in local revenue (PAD) in North Lombok Regency.